Transnational networks for the restitution of exiled women’s poetry during Franco’s regime: Ernestina de Champourcin and Concha Lagos (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
This article examines the actions taken by the poet Concha Lagos within the literary circuit of Francoist Spain to restore the poetry of exiled female authors, focusing on her relationship with Ernestina de Champourcin. To carry out this analysis, the study explores Champourcin’s participation as an author in the Ágora project led by Lagos, examines their correspondence, and reconstructs the dialogue they established through their poetic proposals. The research is framed within the field of Spanish transnational studies and engages with the notion of responsibility and the consequences of exercising it under Francoism.
Keywords: Spanish transnational networks; responsibility; Republican exile; anti-Francoism; poetry written by women